2019 IEEE Symposium Series on Computational Intelligence (SSCI) 2019
DOI: 10.1109/ssci44817.2019.9002942
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamic Multi-objective Optimization via Regression Transfer Learning

Abstract: Dynamic multi-objective optimization problems (DMOPs) remain a challenge to be settled, because of conflicting objective functions change over time. In recent years, transfer learning has been proven to be a kind of effective approach in solving DMOPs. In this paper, a novel transfer learning based dynamic multi-objective optimization algorithm (DMOA) is proposed called regression transfer learning prediction based DMOA (RTLP-DMOA). The algorithm aims to generate an excellent initial population to accelerate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Experimental results confirmed that this method outperformed three other prediction-based DMOAs. Wang et al [165] introduced a regression transfer learning model that incorporates SVR to predict the PS of DMOPs. They compared the algorithm with three state-of-the-art algorithms using benchmark functions.…”
Section: Dmoas Based On Transfer Learningmentioning
confidence: 99%
“…Experimental results confirmed that this method outperformed three other prediction-based DMOAs. Wang et al [165] introduced a regression transfer learning model that incorporates SVR to predict the PS of DMOPs. They compared the algorithm with three state-of-the-art algorithms using benchmark functions.…”
Section: Dmoas Based On Transfer Learningmentioning
confidence: 99%
“…Nonlinear models are developed to capture the nonlinearity of environmental changes. In [149], an regression transfer learning model embedding a support vector regressor is proposed to predict the PS of DMOPs over time.…”
Section: Prediction Based Approachesmentioning
confidence: 99%
“…3) Machine learning models improve change response. Transfer learning [73,149] is one of the machine learning techniques that have proven to learn from dynamic environments efectively and respond to environmental changes to a great standard. 4) Preference/reference-driven approaches simplify the search for solutions to DMOPs and therefore alleviate the complexity of change response by focusing on special points of interest to decision makers [175].…”
Section: Lessons Learnt From the Development Of Edmomentioning
confidence: 99%